2011
DOI: 10.1016/s1995-7645(11)60076-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic malaria parasitemia does not induce additional oxidative stress in pregnant women of South East Nigeria

Abstract: Asymptomatic malaria parasitemia does not induce additional oxidative stress on pregnant women in Nigeria. The enormity of acute and complicated attack should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Intestinal epithelial cells are important sensors of microbial infection. Intestinally derived transformed cell lines produce a variety of pro-inflammatory mediators in response to intracellular infection with bacteria including interleukins 1 and 8 cyclooxygenase-2 and inducible nitric oxide synthase [16][17][18][19][20][21] . Several of these mediators cause activation of neutrophils and macrophages, providing a mechanism by which intestinal epithelial cells import these cells to the site of pathogen invasion.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal epithelial cells are important sensors of microbial infection. Intestinally derived transformed cell lines produce a variety of pro-inflammatory mediators in response to intracellular infection with bacteria including interleukins 1 and 8 cyclooxygenase-2 and inducible nitric oxide synthase [16][17][18][19][20][21] . Several of these mediators cause activation of neutrophils and macrophages, providing a mechanism by which intestinal epithelial cells import these cells to the site of pathogen invasion.…”
Section: Disscussionmentioning
confidence: 99%
“…As a result, lipid peroxidation causes changes in membrane permeability and selectivity and ultimately leads to alterations in cell volume homeostasis and cellular metabolism. Moreover, hydroperoxides and aldehydes are directly toxic to cells and organelles, have neutrophil chemotactic properties and may regulate cytokine production [16][17][18][19][20][21][22] .…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported asymptomatic malaria in Nigeria (Achidi et al, 1995; Anorlu et al, 2001; Jeremiah and Uko, 2007; Kotila et al, 2007; Nwagha et al, 2011; Nwagha et al, 2009; Nwaneri et al, 2013; Ojurongbe et al, 2011). However, these studies are mostly descriptive and extensive analytical studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The resultant effect is the generation of enormous free radicals and initiation of oxidative stress which have been implicated in uncountable perinatal and maternal illnesses. [6][7][8] Antioxidants include organic molecules (minerals and vitamins), enzymes, and dietary chemicals (phytochemicals) used in preventing the effects of oxidative stress. Defence against oxidative stress is largely dependent upon an orchestrated synergism between some of these endogenous and exogenous antioxidants.…”
Section: Introductionmentioning
confidence: 99%